Effects of the Global Financial and Economic Crisis on the Bolivian economy: A CGE approach - Martin Cicowiez; Carlos Gustavo Machicado (Institute for Advanced Development Studies (INESAD), 2010)
This paper analyses the impact of the Global Financial Crisis on the Bolivian economy. The PEP 1-1 Standard Model has been employed to analyze the effects of a reduction in (i) the world export prices of mining and agriculture, (ii) the world demand of textiles, and (iii) transfers to households (i.e., remittances) from abroad. The model has been calibrated to a new 2006 SAM for Bolivia. The households have been disaggregated according to their location (urban and rural) and ethnicity (indigenous and non-indigenous). The factors of production have been disaggregated into skilled and unskilled labor, capital, and natural resources. Not surprisingly, our results highlight the relevance of the decrease in the export price of natural gas in explaining the negative effects of the Global Financial Crisis.
Keywords: C68; G01; E17; 330; Computable General Equilibrium Model; Financial Crisis; Forecasting and Simulation; Finanzmarktkrise; Makroökonomischer Einfluss; CGE-Modelling; Allgemeines Gleichgewicht; Social Accounting Matrix; Bolivien